Semi-anaerobic Growth Conditions are Favoured by some Escherichia coli Strains During Heterologous Expression of Some Archaeal Proteins - Demir, Volkan; Dincturk, H Benan (Springer Science and Business Media LLC, 2006)
Host cell physiology is known to play a crucial role in the expression of foreign genes in heterologous systems. Expression of archaeal genes in anaerobic or semi-anaerobic growth conditions of E. coli has been previously reported to be a means of improving solubility of some proteins. Here, we report that some of the Rosetta strains of E. coli, which harbour the rare tRNA genes for the expression of archaeal genes, favour semi-anaerobic conditions for the expression of putative FMN binding domain of glutamate synthase from Methanocaldococcus jannaschii at low inducer concentrations.
Keywords: Archaeal Proteins; Glutamate Synthase; Methanococcales; Escherichia coli; Gene Expression; Anaerobiosis; Cell Proliferation